Managing IT workers - Łubieńska, Katarzyna; Woźniak, Jacek (Business, Management and Economics Engineering, 2012)
The text analyses the issue of motivation in software engineers. It bases on the experiences of one of the authors, and on preliminary results of qualitative and quantitative research gathered from 300 software engineers working in the IT financial service sector in Poland. It reviews main approaches to software specialist motivation found in the scientific and practical literature. It critiques some approaches to motivation of software specialists for the long-term consequences of using the motivators that they focus on. It shows that research based on P. Glen’s model (2003a) analyses only hygienic factors (as described by Herzberg) that can hinder the state of flow (Csikszentmihalyi 1975), which is characteristic of internally motivated software specialists. There are no analyses which would show how to secure long-term hygienic factors in the management of IT specialist motivation. Recommendations on long-term hygienic factors form a significant part of the text.